A new Buchananiella Reuter (Hemiptera: Anthocoridae) from Indochina and the Malay Peninsula, with a note on B. crassicornis Carayon - Yamada, Kazutaka; Hirowatari, Toshiya (Zootaxa, 2007)
A new flower bug, Buchananiella atrata, is described based on recently collected specimens from Indochina and the Malay Peninsula; and Buchananiella crassicornis Carayon is recorded from Thailand for the first time. Buchananiella atrata Yamada and Hirowatari, new species, is closely allied to the latter species, from which it is separable by rostral segment III being blackish brown with pale yellow apex, the entirely blackish brown femur, and the paramere being apically modified into a acute projection and a swollen portion.